What Does the Public Know about Economic Policy, and How Does It Know It? - Alan S. Blinder; Alan B. Krueger (Institute for the Study of Labor (IZA), 2004)
Public opinion influences politicians, and therefore influences public policy decisions. What are the roles of self-interest, knowledge, and ideology in public opinion formation? And how do people learn about economic issues? Using a new, specially-designed survey, we find that most respondents express a strong desire to be well informed on economic policy issues, and that television is their dominant source of information. On a variety of major policy issues (e.g., taxes, social security, health insurance), ideology is the most important determinant of public opinion, while measures of self-interest are the least important. Knowledge about the economy ranks somewhere in between.
Keywords: E60; D70; 330; ideology; public opinion; knowledge; Öffentliche Meinung; Public Choice; Eigeninteresse; Ideologie; Bildung; Interview; Vereinigte Staaten